KESALAHAN SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA PADA MATERI SPLDV : SYSTEMATIC LITERATURE REVIEW - Aulia Adytia Putri; Nanang Priatna (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2023)
Mathematics education is crucial for survival, therefore it is expected that students have good mathematical ability and attitude, one of which is the ability to solve mathematical problems so that there are no more mistakes in solving problems on the SPLDV material. The ability to solve mathematical problems is one of the abilities that students must have in the 21st century. This research will examine literature using a systematic literature review related to how students make mistakes in solving mathematical problems on the SPLDV material. The literature criteria used in this study are journal articles indexed by Sinta or Google Scholar with a maximum publication year of the last 5 years (2019-2023). The purpose of this study is to identify, review, and draw conclusions from relevant literature on how students make mistakes in solving mathematical problems on the SPLDV material. By conducting this research, it can provide information related to how students make mistakes in solving mathematical problems on the SPLDV material as well as opportunities to conduct research on student mistakes in solving mathematical problems on other materials.